2023
DOI: 10.3389/fpsyg.2022.1035021
|View full text |Cite
|
Sign up to set email alerts
|

Dense is not green: How visual density influences greenness evaluation on environmentally friendly products

Abstract: IntroductionThe visual design of environmentally friendly products has a strong influence on consumer decisions. The study offers a novel insight, suggesting that consumers' perceptions of environmentally friendly products may be affected by the visual density design.MethodsFour experiments tested the effect of visual density on the perceived greenness of environmentally friendly products.ResultsStudy 1 showed that perceived greenness was higher for environmentally friendly products with low visual density des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Previous research has shown that displaying green products influences consumer attitudes and behaviors. For instance, in terms of display forms, Wang et al (2020) found that when consumers are psychologically distant from environmental issues, upward displays of eco-friendly products can improve their processing fluency of product information, resulting in more favorable product evaluations and higher purchase intentions (Xiao et al, 2023) showed that perceived greenness was higher for environmentally friendly products with low visual density design. In addition, regarding the display environment, Yao (2023) demonstrates that displaying products with green attributes renders green products more recognizable to the consumer, thereby inducing green choices among the consideration sets.…”
Section: Green Productmentioning
confidence: 99%
“…Previous research has shown that displaying green products influences consumer attitudes and behaviors. For instance, in terms of display forms, Wang et al (2020) found that when consumers are psychologically distant from environmental issues, upward displays of eco-friendly products can improve their processing fluency of product information, resulting in more favorable product evaluations and higher purchase intentions (Xiao et al, 2023) showed that perceived greenness was higher for environmentally friendly products with low visual density design. In addition, regarding the display environment, Yao (2023) demonstrates that displaying products with green attributes renders green products more recognizable to the consumer, thereby inducing green choices among the consideration sets.…”
Section: Green Productmentioning
confidence: 99%